Starting age and L1 & L2 interaction - Mihaljević Djigunović, Jelena (2008)
The paper describes a study in which performance of two groups of young learners on communicative tests in L2 is compared to their performance on the same type of tests in their L1. Analyses of results across skills and languages will point to different L1¸and L2 interactions between younger and older beginners. Theoretical and practical implications of findings are discussed.
Projekt MZOS
ENG